A Single Mutation is Sufficient to Modify the Metal Selectivity and Specificity of a Eukaryotic Manganese Superoxide Dismutase to Encompass Iron. Issue 20 (12th December 2017) - Hunter, Thérèse; Bonetta, Rosalin; Sacco, Anthony; Vella, Marita; Sultana, Paul‐Michael; Trinh, Chi H.; Fadia, Hava B. R.; Borowski, Tomasz; Garcia‐Fandiño, Rebeca; Stockner, Thomas; Hunter, Gary J.
Abstract: We have generated a site‐directed mutant of the manganese superoxide dismutase SOD‐3 of C.elegans (MnSOD‐3) which modifies the metal specificity of the enzyme. While wild‐type MnSOD‐3 functions with manganese in the active site (3600 U mg −1 of protein) it has little or no activity when iron is incorporated. However, when histidine replaces glutamine 142 in the active site, the enzyme retains 50 % of its activity and becomes cambialistic for its metal cofactor exhibiting very similar specific activity with either manganese or iron. Abstract : Iron manganese and cambialistic mutants : A site‐directed mutant of the manganese superoxide dismutase SOD‐3 of C.elegans (MnSOD‐3) has been generated that modifies the metal specificity of the enzyme. While wild‐type MnSOD‐3 functions with manganese in the active site (3600 U mg −1 of protein) it has little or no activity when iron is incorporated. However, when histidine replaces glutamine 142 in the active site, the enzyme retains 50 % of its activity and becomes cambialistic for its metal cofactor exhibiting very similar specific activity with either manganese or iron.